Hydropericardium syndrome (HPS)-an embryo infectivity study - MADHUMATHI, B G; GOWDA, R N SREENIVASA; VIJAYASARTHI, S K; GOPALAKRISHNA, S; SATYANARAYANA, M L (The Indian Journal of Animal Sciences, 2014)
Hydropericardium syndrome (FAV -type 4) was experimentally induced in 9-day-old embryos via yolk sac route and in 11-day-old embryos via allantoic sac route. The infected embryos were sequentially harvested from 2DPI onwards up to 6 DPI and various gross and histopathological lesions were systematically recorded. Gross lesions in infected embryos inboth the routes of inoculation were characterized by dwarfing, curling of toes, congestion, petechiae all over the body,pale/green livers or necrotic/dark livers, hepatomegaly, pale/parboiled heat, hydropericardium, splenomegaly and urate deposition in kidneys. Histological lesions observed in infected embryos were varying degrees of congestion, haemorrhage, edema, infiltration of lymphocytes and heterophils and various degenerative changes in heart, spleen, liver and kidneys. Presence of basophilic intranuclear inclusion body in hepatocytes was a characteristic feature. The intensity of gross and histopathological lesions were higher in yolk sac route in comparison to that of allantoic sac route.